Multi-modality cardiac imaging in the management of diabetic heart disease - Wamil, Malgorzata; Goncalves, Marcos; Rutherford, Alexander; Borlotti, Alessandra; Pellikka, Patricia Ann (Frontiers in Cardiovascular Medicine, 2022)
Diabetic heart disease is a major healthcare problem associated with an increased risk of serious complications and high mortality. Patients with diabetes show an excess risk of death for cardiovascular causes, twice as high as the general population and those with diabetes type 1 and longer duration of the disease present with more severe cardiovascular complications. Among the many complications of diabetes, coronary artery disease and heart failure deserves special consideration as the leading causes of morbidity and reduced life expectancy. Multimodality cardiac imaging, including echocardiography, cardiac computed tomography, and cardiac magnetic resonance play crucial role in the diagnosis and management of different pathologies included in the definition of diabetic heart disease. In this review we summarise the utility of multi-modality cardiac imaging in characterising ischaemic and non-ischaemic causes of diabetic heart disease and give an overview of the current clinical practice. We also describe emerging imaging techniques enabling early detection of coronary artery inflammation and the non-invasive characterisation of the atherosclerotic plaque disease. Furthermore, we discuss the role of MRI-derived techniques in studying altered myocardial metabolism linking diabetes with the development of diabetic cardiomyopathy. Finally, we discuss recent data regarding the use of artificial intelligence applied to large imaging databases and how those efforts can be utilised in the future in screening of patients with diabetes for early signs of disease.